Incidence of Pedagogical Leadership in Students' Performance in Higher Education - Palomino Fernández, José Manuel; Cáceres Reche, María Pilar; Pérez Pérez, Lucía; Ramos Navas-Parejo, Magdalena (International Journal of Educational Organization and Leadership, 2023)
Since the creation of the European Higher Education Area (EHEA) in 1999, the development of new teaching models, in which the student takes responsibility for their learning, has been favored. In this educational context, pedagogical leadership, understood as that oriented to the improvement of student achievement and performance, is presented as a response capable of promoting and improving both the quality of higher education and the teaching-learning processes. This study is intended to analyze the incidence of pedagogical leadership in higher education institutions from the most current scientific literature. Pedagogical leadership can be defined as a leadership that will have an influence on the student's performance. For this, a systematic review was carried out in the Web of Science and Scopus databases. Seventeen of the 288 articles reviewed were accepted. Therefore, the representation in the scientific literature of leadership aimed at improving student performance in higher education is still limited and incipient. As main contributions, the need to incorporate this leadership model in higher education institutions is highlighted, as an element of change and improvement of quality in them, as well as to evaluate the results obtained after its incorporation in higher education.
Keywords: academic performance; e-leadership; higher education; pedagogical leadership; systematic review; Scopus